Teaching Vocabulary at the Upper Primary Levels with the Vocabulary Self-Selection Strategy - Kang, Natalie; Netto-Shek, Jo-Ann (Beyond Words, 2017)
In this paper, the authors describe a classroom inquiry by a newly graduated English language teacher on the explicit teaching of vocabulary with one class of 40 pupils at the upper primary levels through the Vocabulary Self-Collection Strategy (VSS) (Haggard, 1982, 1986; Ruddell, 2008a). Findings from this inquiry reveal that the VSS strategy designed primarily for the development of vocabulary in academic or content areas in learners was also suitable for the learning of thematically-related words in fiction texts as well. In addition, it is argued that since the strategy was new to this class of pupils, prioritising word study skills over the identification of key words in a text is a useful primer to the use of the strategy. The article ends with the implications of the strategy implementation on the pupils, the teacher and her own classroom practice as an English language teacher.